Estimating Gross Primary Production (GPP) of Kelantan forest area using MODIS - Alias, Nor Lianatashya (2020)
Kelantan state is located in the north-eastern of Peninsular Malaysia, with 5.8 million hectares is covered by forested areas. Gross primary production (GPP) is the amount of carbon captured by plants and it is an important biophysical parameter in the spatio-temporal dynamics of CO2. GPP estimates derived from the Moderate Resolution Imaging Spectroradiometer (MODIS) are converted to the forest area and compared. GPP is estimated through a light use efficiency model (LUE) and enhanced vegetation index (EVI) as a proxy of greenness to address spatial and temporal variation in terrestrial photosynthetic activities. This study is important because the output will be used as a reference to estimate the approximate total carbon in Kelantan. Estimation GPP of Kelantan state is also useful for natural resource and land management, regional carbon cycle analysis, ecosystem status assessment, and environmental change monitoring. The objective of this study is to estimate Gross Primary Production (GPP) value of forested area in Kelantan using MODIS EVI data. The MODIS data products was taken and downloaded from The Level-1 and Atmosphere Archive & Distribution System (LAADS) Distributed Active Archive Center (DAAC) website. The products of MOD15 FPAR and MOD17A2H were analyzed using ENVI version 5.1 and ArcMap version 10.3 software. The GPP was extracted from MOD 17A2H product to go through an images processing steps, image analysis which MOD 15 algorithm and MOD 17 algorithm. The image was classified into different classes of range in image classifications. The results show that GPP was highest at areas in Gua Musang is Felda Chiku which is main vegetation detected was oil palm and also surrounded by forest area. While the lowest area is around Kota Bharu, Tumpat and Bachok which lot of development are found around there. In conclusion, the estimation of GPP of forested area in Kelantan can be calculated using MODIS EVI data.